2016
DOI: 10.4314/sajas.v46i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymorphisms in the ABCG2, LEPR and SCD1 genes on milk production traits in Holstein cows

Abstract: This study was performed to investigate the association between polymorphisms in the ABCG2 (ATPbinding cassette sub-family G member 2), LEPR (leptin receptor) and SCD1 (stearoyl-coenzyme A desaturase 1) genes and milk production traits in Holstein dairy cows in Iran. The analysis was conducted on 816 lactations from 408 Iranian Holstein cows. Genotyping was carried out using the PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) technique. The results of the association study reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The potential use of genetic polymorphism, particular polymorphism of ABCG2, GH, and GHR genes in some cattle breeds as functional candidates for production traits have been documented in several reports (Lucy et al, 1998;Zhou et al, 2005;Hadi et al, 2015;Ghombavani et al, 2016). In this study we described the use of these markers with three cattle populations, Egyptian native (Baladi), Holstein Friesian and Hybrid cattle, to find out if these markers can be used with these different cattle population for selection and improvement of milk quality and milk yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential use of genetic polymorphism, particular polymorphism of ABCG2, GH, and GHR genes in some cattle breeds as functional candidates for production traits have been documented in several reports (Lucy et al, 1998;Zhou et al, 2005;Hadi et al, 2015;Ghombavani et al, 2016). In this study we described the use of these markers with three cattle populations, Egyptian native (Baladi), Holstein Friesian and Hybrid cattle, to find out if these markers can be used with these different cattle population for selection and improvement of milk quality and milk yield.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the GHR gene alter GH functions by changing the protein's ability to bind to this receptor on target cells (Maskur and Arman 2014). Several reports documented the association between milk yield and composition in cattle and the polymorphism in ABCG2 (Mousavizadeh et al 2013;Ghombavani et al, 2016), GH (Ge et al, 2003;Kim et al, 2004;Mullen et al, 2010;Komisarek et al, 2011;Mullen et al, 2011), and GHR genes (Blott et al, 2003;Maj et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Komisarek et al [53] reported a significant effect of ABCG2 gene polymorphisms on estimated breeding values for milk fat production traits, calving-to-first insemination interval, and non-return rate in Polish Holstein-Friesian cattle. Genetic effects of ABCG2 polymorphism on milk production traits were also reported in the Holstein cattle [54,55]. Zhang et al [28] elicited that SLC11A1 gene polymorphisms are not associated with somatic cell score and milk yield in Chinese Holstein.…”
Section: Discussionmentioning
confidence: 94%
“…Genotypic frequencies of AA, AC and CC were 0.83, 0.15 and 0.02 whereas the allelic frequencies for A and C allele were 0.91 and 0.19, respectively (Table 5). Soltani-Ghombavani et al (2016) in Iranian Holstein cattle also observed a much higher frequency of A allele compared with C allele (97% vs. 3%) of the ABCG2-Y581S locus. Development of crossbred cattle started, by crossing Tharparkar (T) as a Zebu breed and three exotic breeds, namely, Holstein Friesian (H), Brown Swiss (B) and Jersey (J) at National Dairy Research Institute, Karnal.…”
Section: Average Test Day Fat Percentage In Karan Fries Cattlementioning
confidence: 85%